Test and research on mechanical characteristics of geotechnical filling engineering based on inclined soft ground. (10th May 2021) - Wei, Jing; Zeng, Xinfa
In order to improve the analysis accuracy of the mechanical properties of soil filling in inclined soft soil foundation, the experimental research method of engineering mechanical properties of rock and soil filler based on inclined soft soil foundation was put forward. CEO-SLOPE software is used to simulate the deformation and stress of foundation and embankment in the process of rock-soil filling. The mechanical properties of bedrock and filling engineering in inclined soft soil are obtained. From the test results, it can be seen that the filling load will compacted the soil of the inclined soft foundation, leading to deformation phenomena such as expansion and sloshing at the foot of the slope.